Heritage of the Soviet Ideology in parenting nowadays : the case of Latvia - Rubene, Zanda; Jansone-Ratinika, Nora; Dinka, Ilze (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2015)
The Soviet period has shaped the history of Latvia in different areas. This article offers an insight into the ideological heritage which has significantly transformed the pedagogical discourse in theoretical as well as instrumental level. Article describes a part of two researches “Social transformations of the child's image in children's room” and “Father`s Pedagogical Competence in Family Nowadays”, revealing common features characterizing Soviet issues. Narrative explores crucial systemic changes, transformation of social and family life, deals with the deformed relationship between individuals in public sphere and family members in private and shows consequences still actual nowadays, pointing out the question of gendered and “Sovietized” identities.